Role of magnetic resonance imaging before initial biopsy: comparison of magnetic resonance imaging‐targeted and systematic biopsy for significant prostate cancer detection - Haffner, Jérémie; Lemaitre, Laurent; Puech, Philippe; Haber, Georges‐Pascal; Leroy, Xavier; Jones, J. Stephen; Villers, Arnauld (BJU international, 2011)
Study Type – Diagnostic (exploratory cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? The strategy of prostate targeted biopsies to a multi‐parametric magnetic resonance imaging (mp‐MRI)‐suspicious area was shown to improve biopsy results. Strategy of targeted biopsies only was not evaluated. In this article we propose that use of pre‐biopsy mp‐MRI within the diagnostic pathway would result in an enhanced detection of clinically significant disease, fewer men diagnosed with clinically insignificant disease, fewer men biopsied overall and fewer needle deployments in those that are. OBJECTIVE • To compare magnetic resonance imaging (MRI)‐targeted biopsies with extended systematic biopsies for the detection of significant prostate cancer. METHODS • In all, 555 consecutive patients with suspicion of prostate cancer had pre‐biopsy dynamic contrast‐enhanced 1.5‐tesla (T) MRI with pelvic coil, 10–12 transrectal ultrasound‐guided extended systematic biopsies plus two targeted biopsies at any MRI area suspicious for malignancy. • Significant prostate cancer was defined as >5 mm total cancer length and/or any Gleason pattern >3. • Cancer length and grade at biopsy were reported and located on a 24‐sector map. RESULTS • Median (range) prostate‐specific antigen (PSA) was 6.75 (0.18–100) ng/mL. • MRI was positive in 351 (63%) patients and, overall, 302 (54%) had cancer at extended systematic biopsies and/or targeted biopsies. Of 302 cancers detected, 249 (82%) were significant prostate cancers and 53 (18%) were nonsignificant prostate cancers. • Extended systematic biopsies did not detect 12 significant prostate cancers and targeted biopsies did not detect 13 significant prostate cancers. For significant prostate cancer detection, sensitivity, specificity and accuracy of targeted biopsies were 0.95, 1.0 and 0.98. The values for extended systematic biopsies were 0.95, 0.83, and 0.88. • The detection accuracy of significant prostate cancer by targeted biopsies was higher than that by extended systematic biopsies (P < 0.001). Targeted biopsies also detected 16% more grade 4/5 cases and better quantified the cancer than extended systematic biopsies, with cancer length of 5.56 vs. 4.70 mm (P= 0.002). • A targeted biopsies‐only strategy without extended systematic biopsies would have necessitated a mean of 3.8 cores performed in only 63% of patients with positive MRI and avoided the potentially unnecessary diagnosis of 13% (53/302) of nonsignificant prostate cancers. CONCLUSIONS • Strategy of targeted biopsies alone at pre‐biopsy MRI‐suspicious areas is an attractive potential alternative to extended systematic biopsies for detection of significant prostate cancer. • Further studies are necessary to validate the strategy of targeted biopsies alone.